Discontinuous switching of position of two coexisting phases. (27th July 2018) - Krüger, Samuel; Weber, Christoph A; Sommer, Jens-Uwe; Jülicher, Frank
Abstract: Liquid–liquid phase separation leads to the formation of condensed phases that coexist with a fluid. Here we investigate how the positions of a condensed phase can be controlled by using concentration gradients of a regulator that influences phase separation. We consider a mean field model of a ternary mixture where a concentration gradient of a regulator is imposed by an external potential. A novel first order phase transition occurs at which the position of the condensed phase switches in a discontinuous manner. This mechanism could have implications for the spatial organisation of biological cells and provides a control mechanism for droplets in microfluidic systems.